Epistemic Injustice and anti-media populism in the Philippines - Tubera, Kurt Christian B (Animo Repository, 2024)
Anti-media populism—a form of populism that emphasizes elite hostility towards the media—is an understudied case in the Philippines. Rodrigo Duterte’s administration, which is widely argued in the literature as performative of an anti-media populist leadership, silenced three media outlets: (1) ABS-CBN, (2) The Philippine Daily Inquirer, and (3) Rappler. In these cases, the journalists are hindered from disseminating accurate information to the public because of anti-media populism’s delegitimizing effect. However, the literature lacked an analysis of the epistemic harms inflicted by the political ideology. It is crucial to address this lacuna insofar as injustices related to accurate information dissemination heavily impact journalists and the general public as epistemic subjects (that is, subjects with a set of agencies concerning seeking, receiving, and imparting knowledge). Identifying injustices of the epistemic sort should complement the literature in identifying harms and counterstrategies against the delegitimizing effect of anti-media populism. In light of this problem, this paper offers an epistemic analysis of anti-media populism in the Philippines. I claim that anti-media populism causes epistemic injustice. Miranda Fricker defines epistemic injustice as a harm inflicted against one’s capacities as a subject of knowledge. I argue that, in cases of anti-media populism, journalists are being harmed as informants. To support this argument, I utilize Gaile Pohlhaus’s lens of epistemic relations to identify two categories where journalists (qua informants and inquirer) are harmed: (1) stymieing epistemic relations, and (2) fracturing epistemic trust. This paper hopes to stress the need to address the epistemic injustice caused by anti-media populism.